(untitled) (Bioscience Journal, 2022)
We optimized the expression and purification of outer membrane proteins SpaO and LamB from Salmonella typhi. We investigated various factors in the expression and purification processes, including the use of isopropyl β-d-1 thiogalactopyranoside (IPTG), imidazole, and urea. First, PCR amplification was carried out on SpaO and LamB genes. The genes were then cloned in pTZ57R/T, and then expressed in pET28a vector and transformed into Escherichia coli BL21 (DE3). Gene insertion was confirmed by enzymatic digestion with NdeI and XhoI. Inclusion bodies expressing recombinant SpaO and LamB were induced with 200 and 400 µL 0.5 mM IPTG, respectively. The formed protein inclusion bodies were then isolated from the pellet and solubilized in IB buffer containing 8 M urea for SpaO and 6 M urea for LamB. Proteins were refolded by dialysis in 3M urea. Purified proteins with nickel-nitrilotriacetic acid affinity chromatography and eluted with buffer containing 250 mM imidazole for SpaO and 150 mM imidazole for LamB. The protein expression profiles were analyzed by SDS-PAGE, which identified the 33 and 49 kDa bands corresponding to rSpaO and rLamB. Western blotting Purification was carried out by nickel affinity resin with 250 mM and 150 mM imidazole for rSpaO and rLamB and refolded through stepwise dialysis with anti-His tag antibodies confirmed their expression. These optimized methods can be used to generate recombinant proteins for the development of future vaccines.